Inter(net)linked - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Inter(net)linkedNational agricultural research institutions in the Third World can now be linked, at no cost, to the Internet and World Wide Web. This service, which is provided by the International Service for National Agricultural Research...